Respuestas
Respuesta dada por:
9
Trinomio cuadrado perfecto:
(x+6)^2=
(x)^2+2(x)(6)+(6)^2
x^2+12x+36
SALUDOS
(x+6)^2=
(x)^2+2(x)(6)+(6)^2
x^2+12x+36
SALUDOS
Respuesta dada por:
3
Es un producto notable en el cual se aplica la forma:
![(a+b)^2= a^2+2ab+b^2 (a+b)^2= a^2+2ab+b^2](https://tex.z-dn.net/?f=%28a%2Bb%29%5E2%3D+a%5E2%2B2ab%2Bb%5E2)
Entoncess:
![{(x+6)^2=}\\{ (x)^2+2(x)(6)+(6)^2=}\\{x^2+12x+36 {(x+6)^2=}\\{ (x)^2+2(x)(6)+(6)^2=}\\{x^2+12x+36](https://tex.z-dn.net/?f=%7B%28x%2B6%29%5E2%3D%7D%5C%5C%7B+%28x%29%5E2%2B2%28x%29%286%29%2B%286%29%5E2%3D%7D%5C%5C%7Bx%5E2%2B12x%2B36)
Entoncess:
Preguntas similares
hace 6 años
hace 9 años
hace 9 años